Bundesbericht Wissenschaftlicher Nachwuchs 2017 Statistische Daten und Forschungsbefunde zu Promovierenden und Promovierten in Deutschland - Bundesbericht Wissenschaftlicher Nachwuchs, Konsortium (W. Bertelsmann Verlag, 2017)
This report provides the reader with empirical findings on junior researchers in Germany. The reconciliation of family and an academic career constitutes the central issue of the report. Other topics are work and employment conditions, qualification conditions during the doctoral phase, as well as career paths and perspectives, particularly during the post doctoral phase. Topics such as mobility behaviour and contributions to the research, teaching, and transfer of junior scientists as well as the educational returns of a doctoral degree are also addressed. The report is primarily based on data from official statistics and surveys conducted on a regular basis. At the same time, the paper examines the collected data with greater emphasis on the comparability and classification of the findings. In doing so, the report provides universities, research institutes, interest groups, funding agencies, and decision makers at federal and state level with essential knowledge on the topic.